Pathogenic cellular role of the p.L104P human cationic trypsinogen variant in chronic pancreatitis - Balázs, Anita (Am J Physiol Gastrointest Liver Physiol, 2016)
Mutations in the PRSS1 gene encoding human cationic trypsinogen are associated with hereditary and sporadic chronic pancreatitis. High-penetrance PRSS1 mutations found in hereditary pancreatitis alter activation and/or degradation of cationic trypsinogen, thereby promoting intrapancreatic trypsinogen activation. In contrast, a number of rare PRSS1 variants identified in subjects with sporadic chronic pancreatitis cause misfolding and endoplasmic reticulum (ER) stress. Mutation p.L104P is unique among natural PRSS1 variants, since it affects the substrate binding site of trypsin. The aim of the present study was to establish the clinical significance of variant p.L104P through functional analysis. We found that p.L104P trypsin exhibited decreased activity on peptide and protein substrates; however, autoactivation was slightly accelerated. Remarkably, binding of the physiological trypsin inhibitor serine protease inhibitor Kazal type 1 (SPINK1) was decreased by 70-fold. In the presence of the trypsinogen-degrading enzyme chymotrypsin C, mutant p.L104P autoactivated to higher trypsin levels than wild-type trypsinogen. This apparent resistance to degradation was due to slower cleavage at Arg(122) rather than Leu(81). Finally, secretion of mutant p.L104P from transfected cells was markedly reduced due to intracellular retention and aggregation with concomitant elevation of ER stress markers. We conclude that PRSS1 variant p.L104P exhibits a variety of phenotypic changes that can increase risk for chronic pancreatitis. Mutation-induced misfolding and associated ER stress are the dominant effects that support a direct pathogenic role in chronic pancreatitis.